THE IMPACT OF LIQUIDITY AND SOLVABILITY TOWARD PROFITABILITY ON FOOD AND BEVERAGE PRODUCT SUBSECTORS COMPANIES THAT LISTED IN INDONESIA STOCK EXCHANGE - Bill Schara Marbun; Harman Malau (Jurnal Ekonomis, 2020)
This aim of this research was to know whether the liquidity and solvency variables have impact on probability in the food and beverages product subsector. The data source of this research was secondary data obtained from financial reports and annual reports of companies listed on the Indonesia Stock Exchange in 2016-2018. Then this study used purposive sampling to determine the sample that in research. And several methods of data analysis that to be processed, with test classic assumptions, test hypotheses and regression analysis in providing conclusions of this study. It was found that the average liquidity variable in the company was in good condition, solvency in the related company was not good and the same as liquidity, profitability in the average company was in good condition. Meanwhile based on the hypothesis test it was concluded that liquidity has a significant effect on profitability but solvency did not influence profitability. Liquidity and solvency had a significant impact on profitability simultaneously